Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2015
Oblicz wartość wyrażenia: a) 3 1/2*( 2 2/3- 1 5/12)-5/84.44 gwiazdek na podstawie 9 opinii

Oblicz wartość wyrażenia: a) 3 1/2*( 2 2/3- 1 5/12)-5/8

8Zadanie
9Zadanie
10Zadanie
11Zadanie
12Zadanie

a)

`(3 1/2*(2 2/3-1 5/12)-5/8)/(3 3/4-3/4*8 1/3)= ` `(3 1/2* (2 8/12-1 5/12)-5/8)/(3 3/4-strike3^1/4*25/strike3^1)=` `(3 1/2 *1 3/12-5/8)/(3 3/4-25/4)=` 

 

`=(7/2*15/12-5/8)/(3 3/4- 6 1/4)=(105/24-15/24)/(-(6 1/4-3 3/4))=(90/24)/(-(5 5/4-3 3/4))=`    `(30/8)/(-2 2/4)=(15/4)/(-2 1/2)=` 

`=15/4: (-2 1/2)=15/4: (-5/2)=strike15^3/strike4^2* (-strike2^1/strike5^1)=-3/2`    

b)

`(3,75*(2,34+3,86))/(1,759+0,35*8,26)=` `(3,75*(2,34+0,66+3,2))/(1,759+35/100* 8 26/100)=` `(3,75*(3+3,2))/(1,759+ 7/20*8 13/50)=` 

`=(3,75*6,2)/(1,758+ 7/20* 413/50)=` `(3 3/4 * 6 1/5)/(1,759+2891/1000)=(strike15^3/4*31/strike5^1)/(1,759+2,891)=` `(93/4)/(1,759+0,241+2,65)=(93/4)/(4,65)=93/4: 4 65/100=93/4: 4 13/20=93/4: 93/20=strike93^1/4*20/strike93^1=20/4=5` 

`=83/4` 

c)

`(3,6*(2 1/4+4 2/3)-2,3)/(1,32*(3 3/11-2 7/11)+3 3,4)=`  `(3 6/10 * (2 3/12+3 8/12)-2,3)/(1 32/100*(3 14/11-2 7/11)+3,34)=` 

`=(3 3/5* 5 11/12-2,3)/(1 8/25* 1 7/11+3,34)=` `(strike18^3/5* 71/strike12^2-2,3)/(strike33^3/25* 18/strike11^1+ 3,34)=`   `(213/10-2,3)/(54/25+3,34)=` 

`=(21,3-2,3)/(216/100+3,34)=19/(2,16+3,34)=` `19/(5,5)=` `19: 5,5=` 

`19: 5 1/2=19: 11/2=19 * 2/11` `=38/11=3 5/11` 

 

 

` `